PENGARUH POLA ASUH ORANG TUA TERHADAP PENGAMALAN KARAKTER BERTANGGUNG JAWAB REMAJA DI KAMPUNG BUKIT AGUNG KECAMATAN KERINCI KANAN KABUPATEN SIAK - Juwita Turnip; Gimin Gimin; Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the presence of teenagers whose lifestyles are not appropriately done by a teenager who visits from parenting parents, consisting of authoritarian, democratic, and Permissive. Formulation of the problem in this research is: "Is there any significant influence parenting parents (Authoritarian, Democratic, Permissive) against the practice of responsible teen characters" ?. This study aims to determine the effect of significantly Parenting Parents (Authoritarian, Democratic, Permissive) against the practice of Responsible Youth Character. Total population of 974 respondents (adolescents), with sampling using Proportional Random sampling techniques gained 97 Youth. Data collection through questionnaire, interview and observation. Mechanical analysis using quantitative descriptive analysis using Multiple linear regression equation with the process through the program SPSS version 17.00. For a proof of the hypothesis then tested the whole (test F) and partial test to see the effects of each predikator. Results are obtained F count larger than F table (4,331> 2,70) thus rejected Ho Ha accepted, meaning that there is significant influence parenting parents to practice responsible teenage characters in Kampung Bukit Agung Subdistrict Siak Kerinci Kanan. Authoritarian parenting to influence the results obtained sig. (0.174> 0.05) means insignificant, to influence the results obtained parenting Democratic sig. (0.009 <0.05) significant meaning, for the results obtained Permissive parenting sig. (0.109> 0.05) means insignificant. Rated R Square in this study amounted to 0.123, or 12.3%. This means that donations are significant effect between the effect of parenting parents against the practice of responsible teen character is at 12.3%, while 87.7% (100% -12.3%) influenced by other variables not included in this study.Key Words : Parenting Parents, character Responsible Teens.